Clinical effects and emerging issues of atezolizumab plus bevacizumab in patients with advanced hepatocellular carcinoma from Japanese real‐world practice. Issue 4 (24th November 2022) - Nakagawa, Miyuki; Inoue, Masanori; Ogasawara, Sadahisa; Maruta, Susumu; Okubo, Tomomi; Itokawa, Norio; Iino, Yotaro; Obu, Masamichi; Haga, Yuki; Seki, Atsuyoshi; Kikuchi, Yasuharu; Kogure, Tadayoshi; et al.
Abstract: Background: Although the efficacy of atezolizumab has been demonstrated in randomized controlled trials, its long‐term efficacy and association with adverse events in real‐world practice are unknown. This study was designed to shed light on these issues. Methods: In this multicenter retrospective study, data were collected from patients with advanced hepatocellular carcinoma treated with atezolizumab plus bevacizumab in seven institutions in Japan. The authors focused on the efficacy and adverse events related to vascular endothelial growth factor (VEGF) inhibition. Results: A total of 123 patients were enrolled in this study. The median progression‐free survival (PFS) for the first‐line treatment group was 8.0 months (95% confidence interval [CI], 6.1–9.9), whereas the median PFS for the second‐ or later‐line treatment group was 4.1 months (95% CI, 2.6–5.7), which was significantly worse than that of the first‐line treatment group ( p  = .005). Twenty‐seven patients had interrupted bevacizumab treatment. Proteinuria accounted for the largest proportion of bevacizumab treatment interruptions. The cumulative incidence rate of bevacizumab interruption due to anti‐VEGF–related adverse events was significantly higher in patients with hypertension and/or diabetes mellitus than in those without ( p  = .026). The landmark analysis showed that patients experienced bevacizumab interruption by 24 weeks from treatment initiation had poorer PFS than those who did not ( p  = .013). Conclusions: The PFS of atezolizumab plus bevacizumab as first‐line treatment mostly replicates that of a global phase 3 trial. Interrupted bevacizumab treatment was more common in patients with hypertension and/or diabetes mellitus, which may be associated with worsening long‐term PFS. Plain language summary: Atezolizumab plus bevacizumab has been the standard front line systemic therapy for advanced hepatocellular carcinoma. With the growing incidence of fatty liver due to metabolic syndrome as a background liver disease for hepatocellular carcinoma, the rate of comorbid hypertension and diabetes mellitus has been increasing accordingly. The present study demonstrated the cumulative incidence rate of bevacizumab interruption due to anti‐VEGF–related adverse events was significantly higher in patients with hypertension and/or diabetes mellitus. The landmark analysis clarified that interruption of bevacizumab might be a risk of impaired efficacy of atezolizumab plus bevacizumab over the long term in patients with advanced hepatocellular carcinoma. Abstract : This report demonstrated that the cumulative incidence rate of bevacizumab interruption due to anti‐VEGF–related adverse events was significantly higher in patients with comorbid hypertension and/or diabetes mellitus during atezolizumab plus bevacizumab for advanced hepatocellular carcinoma. Interruption of bevacizumab might be a risk of impaired efficacy of atezolizumab plus bevacizumab over the long term in patients with advanced hepatocellular carcinoma.